2022
DOI: 10.1002/jbm.b.35062
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a BMP‐2 gene delivery system for polyetheretherketone bone implant material and its effect on bone formation in vitro

Abstract: Polyetheretherketone (PEEK) has been widely investigated for improving its biological inert to enable it to achieve stronger osteogenic capability and to be a promising material in implant fields. The most important mechanism that makes a successful implantation is osteointegration. Surface modification is an appropriate method to maintain the excellent mechanical properties of PEEK and simultaneously endow PEEK certain biological characters. In this work, we attempted to shape the nanotopography of PEEK surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…are bonded to the PEEK surface in the form of a coating on BMP-2 to provide a functional coating with time-release capability. 107,108 Liu et al 109 compared two modes of BMP-2 loading with covalent binding versus physical adsorption (electrostatic interaction). The results showed that, the loading efficiency was 79.24% for covalent immobilization and 72.36% for rhBMP-2 by heparin physisorption, with significantly lower water contact angles to 77.81 AE 2.21 and 58.01 AE 1.51, respectively.…”
Section: Organic Materials Modified Peekmentioning
confidence: 99%
“…are bonded to the PEEK surface in the form of a coating on BMP-2 to provide a functional coating with time-release capability. 107,108 Liu et al 109 compared two modes of BMP-2 loading with covalent binding versus physical adsorption (electrostatic interaction). The results showed that, the loading efficiency was 79.24% for covalent immobilization and 72.36% for rhBMP-2 by heparin physisorption, with significantly lower water contact angles to 77.81 AE 2.21 and 58.01 AE 1.51, respectively.…”
Section: Organic Materials Modified Peekmentioning
confidence: 99%
“…However, during the reaction, some BMP-2 inevitably loses its activity. Qin et al [15] encapsulated PLGA microspheres to achieve continuous release of BMP-2 nanoparticles, and fixed the microspheres by adhering to the PEEK surface through PDA. In the composite, pBMP-2 release was controlled and the BMP-2 protein was produced continuously and efficiently after transfection, promoting the recruitment, osteogenic induction and differentiation of stem cells on the PEEK surface and accelerating the process of bone repair after PEEK implantation.…”
Section: Fixation Of Bioactive Substancementioning
confidence: 99%